Improved AHP Method and Its Application in Risk Identification - Li, Fengwei; Phoon, Kok Kwang; Du, Xiuli; Zhang, Mingju (Journal of construction engineering and management, 2013)
AbstractThe analytic hierarchy process (AHP) approach has been widely used in multicriteria decision making (MCDM). It is very difficult to meet the consistency requirement of a comparison matrix (CM) in AHP. The authors analyze the reasons for inconsistent CM in AHP and propose an improved AHP (IAHP) to improve CM consistency by using a sorting and ranking methodology. The results of comparing AHP with IAHP by MATLAB simulation show that IAHP is more suitable for solving MCDM problems when the number of elements or factors is 5 or more in MCDM. A case study is presented to illustrate the performance of IAHP when applied to risk identification during an open-cut subway construction. The application results show that IAHP is superior to AHP in terms of CM consistency, information extraction effectiveness, and convenience in practical implementation.